Optimization of Colchicine Concentration by Drop Method for Induction of Variation in Bambara Groundnut Plant (Vigna subterranean L.) - Alisha, Tarra Syifa; Saptadi, Darmawan (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
Bambara groundnut (Vigna subterranea L.) is a legume plant from Africa. This plant is a promising food crop because it has many benefits regarding nutritional content, health, and agronomic aspects. However, efforts to increase the genetic diversity of potential yields are constrained by the limited genetic resources with high yields. Polyploidy induction increases plant diversity by giving chemical mutagens such as colchicine. This study aims to obtain the optimal concentration for the induction of bambara groundnut plant diversity with the drip method. This research was carried out from May 2022 to July 2022, located in the experimental field and at the Plant Breeding Laboratory, Faculty of Agriculture, Brawijaya University. The treatments used were different concentrations of colchicine, namely K0: 0% (control), K1: 0.1%, K2: 0.2%, K3: 0.3%, K4: 0.4%. The analysis of variance with the 5% level test showed that the colchicine concentration treatment significantly affected all observations of the bambara groundnut plant's quantitative character. The coefficient of the diversity of plants treated with colchicine was higher than the control treatment. The concentration used in this study did not cause the death of 50% of plants, so the LC50 value has not been found. Abnormal plants were found at 0.3% and 0.4% colchicine concentrations with different leaf shapes from the control plants.